Geomorphic and sedimentary impact on beaches of Eastern Visayas (Philippines) after Typhoon Haiyan in 2013: short-term recovery and post-depositional changes - Quix, Eva; Engel, Max; Boesl, Fabian; Gonzalo, Lia A. L.; Llanes, Francesca V.; Bahala, Mark A. C.; Eco, Rodrigo C.; Galang, Jan A. M.; Brill, Dominik; May, S. Matthias; Brückner, Helmut (Erdkunde, 2025)
Tropical cyclones and storm surges are a major threat to coastal communities of the Philippines. On 08th November 2013, category 5 Typhoon Haiyan (local name: Yolanda) made landfall on the islands of Eastern Visayas and caused more than 6000 casualties and severe damage to infrastructure and habitats. To assess the geomorphic impact of one of the strongest tropical cyclones on record, three post-typhoon surveys were conducted in 2014, 2015 and 2016 at two severely affected sites on the islands of Leyte and Samar. They aimed at documenting Haiyan-related erosional features and sand deposits. The sites have different geomorphic and geological settings, and exposure to the typhoon track. Differential global navigation satellite system (DGNSS) measurements and sediment analyses were used to document erosion and washover deposition caused by waves and coastal flooding of the beach ridge systems, as well as their recovery and changes over time. Shoreline changes were measured on high-resolution satellite images using the Digital Shoreline Analysis System (DSAS) to determine the typhoon’s impact and recovery potential at a larger spatial scale. The results show the potential to identify storm-wave erosion and washover deposits in sandy ridge sequences across larger time scales. However, fine sedimentary signatures, such as millimetre-scale lamination, may be rapidly overprinted by bioturbation and geomorphic reorganisation of the coast. The coastline tends to return to its pre-storm equilibrium, whereas the pace depends on whether eroded sands remain within reach of the long-term wave regime, on the frequency of subsequent high-category storms and very local geomorphic conditions.
Gesehen am 03.09.2025